Bosnia and Herzegovina : Financial Sector Assessment Program. (IMF Staff Country Reports; Country Report ;, 2015)
This Technical Note presents an update on Banking Sector Supervision Core Principles Implementation in Bosnia and Herzegovina. The system of banking supervision oversight has significantly improved since the last review in 2006, but shortcomings remain. Both supervisory authorities have made progress in enhancing the regulatory framework and supervisory processes since the 2006 Financial Sector Assessment Program. The banking agencies are in the process of preparing a new Law on Banks that should address deficiencies in the supervisory powers, resolution tools, and consolidated supervision. Comprehensive regulations on risk management have been drafted that will address remaining deficiencies that are highlighted in this assessment.